Pengembangan Alat Peraga PATOLOGI (Papan Tol Logika) pada Materi Pernyataan Majemuk - Devin Akbar Albany; Fadhilah Azzahra; Febriandini Muhtasya; Zulkardi Zulkardi; Hapizah Hapizah; Budi Mulyono; Meryansumayeka Meryansumayeka (Jurnal Tadris Matematika, 2022)
This study aims to develop a valid, practical, and effective teaching aid in learning mathematical logic material. The teaching aid developed is Logic Toll Board named PATOLOGI (Papan Tol Logika). The development model used in this study uses the ADDIE development model. The stages of ADDIE development include analysis, design, development, implementation, and evaluation. Data collection was obtained from observation and interviews, then analyzed descriptively. The results of the research that has been carried out indicate that the PATOLOGI teaching aids have been well developed, starting from the analysis stage to the evaluation stage. The tests carried out included testing the validity of teaching aids to experts, practicality tests and effectiveness tests through trial activities with students. The trial results show that students have no difficulty in using teaching aids, so that teaching aids are said to be practical. The trial results also show that the use of visual aids can arouse students' enthusiasm and interest in participating in learning activities, so that students more easily understand the concepts of mathematical logic material, especially compound statements. This shows that the PATOLOGI teaching aids can be categorized as effective. Thus, it is concluded that the PATOLOGI teaching aid is valid, practical, and effective.